Comparative Performance Evaluation of Public Transportation Services in Pokhara Valley - Subedi, Subas; Basnstola, Ramesh; Duwadi, Sandip (Journal of Engineering and Sciences, 2023)
This study conducts the performance evaluation of the public transportation system on the Fewa-Begnas route in Pokhara Valley. The performance evaluation of public transportation is conducted from three perspectives (Economic, operational performance of the vehicle, and passenger perception). Passenger perceptions are assessed based on a survey of 9 indicators. The results obtained from the questionnaire survey are analyzed by calculating the index values. Also, the operational performance of the vehicle is evaluated using 5 indicators (Journey time, Journey speed, Running time, Running speed, and transport system capacity index). Also, for evaluation from an economic perspective, the total cost per km that occurred to run a public bus and the total revenue generated per km are calculated.